Evaluation of treatment of HER2 positive Breast cancer patients with Trastuzumab combined with cytotoxic chemotherapy – a comparative study. (TAJ: Journal of Teachers Association, 2018)
A prospective and retrospective study had been carried out between January 2013 to December 2015 for evaluation of the overall survival (OS) & disease free survival (DFS) rate of HER2 positive breast cancer patients with Trastuzumab combined with cytotoxic chemotherapy and patients who only takes chemotherapy alone. A randomized control trial was run with the 130 patients having HER2 positive breast cancer in the Rajshahi Medical College and Hospital and different private hospitals and Clinics of Rajshahi city. Among 130 women having HER-2 positive breast cancer 52 women were randomly allocated to the TAC (Taxotere, Doxorubicin and Cyclophosphamide) arm and 61 women were randomly allocated to the TAH (Taxotere, Doxorubicin, Herceptin) arm. TAC arm consists of Taxotere (75mg/m2), as 1 hour infusion preceded by Doxorubicin (50mg/m2) and Cyclophosphamide (500mg/m2), both given as an intravenous bolus. This TAC protocol runs for 6 cycles in every 3 weeks. And TAH arm consists of Taxotere (75mg/m2), Doxorubicin (50mg/m2) and Herceptin (8mg/kg for 1st cycle and 6mg/kg from 2nd cycle). In this arm other combined therapy will run till 6 cycles and Herceptin will run up to 12 cycles in every 3 weeks.TAJ 2013; 26: 30-37